Porter family papers - Porter, David, 1780-1843.; Porter, David D. (David Dixon), 1813-1891.
David Porter's papers consist of letters written to his wife, Evelina, and to Samuel Hambleton, James P. McCorkle, and George W. Walker; a draft of his resignation as commander in chief of the Mexican Navy (Armada); and his will. Subjects include Porter's command of the frigate Essex (1811-1814) and of the Mexican Navy (1826-1829) and life in Minorca, Spain, in 1830.
David Dixon Porter's papers include letterbooks, a draft of a letter to William Henry Seward, and printed general orders. A letter from Porter while in New Orleans in 1862 to his wife, George Ann, discussed the life of their southern relatives during the Union occupation of that city. Other correspondents include Nathan Goff, William H. Hunt, and Richard W. Thompson.
Family members represented are David Porter (1780-1843) and his son, David Dixon Porter (1813-1891), naval officers and authors.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: Goff, Nathan, -- 1843-1920 -- Correspondence; Hambleton, Samuel, -- 1777-1851 -- Correspondence; Hunt, William H. -- 1823-1883 -- Correspondence; McCorkle, James P. -- Correspondence; Porter, Evelina Anderson, -- 1790-1871 -- Correspondence; Porter, George Ann Patterson -- Correspondence; Seward, William Henry, -- 1801-1872 -- Correspondence; Thompson, Richard W. -- 1809-1900 -- Correspondence; Walker, George W. -- Correspondence; Porter family; Mexico. -- Armada; Essex (Frigate); Minorca (Spain) -- Social life and customs; New Orleans (La.) -- History -- Civil War, 1861-1865.; Authors; Naval officers